The need to identify occupational exposure to laser radiation in greece. (September 2016) - Makropoulou, M.; Hourdakis, C.J.; Serafetinidis, A.; Sianoudis, I.; Achtipis, A.; Kappas, C.; Tsougos, I.; Maris, T.G.; Gourzoulidis, G.A.
Abstract : Introduction: Optical radiation, part of the non-ionizing spectrum, covers the UV, the IR and the visible regions. The relevant occupational exposure legislation, Directive 2006/25/EC, employs limits and Occupational Health & Safety (OHS) regulations for laser (coherent) and non-coherent artificial optical radiation (AOR). Purpose: Although ten years have passed from the release of the aforementioned Directive, poor progress has been made for its practical implementation, mainly regarding the risk assessment by a qualified expert. The Hellenic Ministry of Labor, following a non-coherent AOR survey, in conjunction with the National Technical University of Athens and the Greek Atomic Energy Commission took the initiative to identify the field. Materials and methods: Lasers are widespread mainly in health care facilities, industry, cosmetic applications, research and entertainment, but there is no homogenized safety approach countrywide. Selected workplaces have been chosen for evaluation of their OHS applied and for measurement of the appropriate optical quantities. The role of the Laser Safety Officer has been discussed as well. Results: Mapping of the extent of laser applications in Greece has been performed together with an initial testing of selected crucial workplaces, as representative pilot studies. Major challenge and objective is the development of dedicated risk assessment checklists and of QA protocols for laser applications, further specified for medical applications. Conclusion: The creation of a national occupational exposure database and of approved safety and QA protocols for laser procedures seems reasonable after the collaboration of the involved Authorities. Disclosure: Authors disclose that they don't have any relationship that may bias their presentation.